Fairness and Incentives in a Multi-Task Principal-Agent Model - Ernst Fehr; Klaus M. Schmidt (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2004)
This paper reports on a two-task principal-agent experiment in which only one task is contractible. The principal can either offer a piece-rate contract or a (voluntary) bonus to the agent. Bonus contracts strongly outperform piece rate contracts. Many principals reward high efforts on both tasks with substantial bonuses. Agents anticipate this and provide high efforts on both tasks. In contrast, almost all agents with a piece rate contract focus on the first task and disregard the second. Principals understand this and predominantly offer bonus contracts. This behavior contradicts the self-interest theory but is consistent with theories of fairness.
urn:nbn:de:bvb:19-epub-335-3
Keywords: C7; C9; J3; 330; Incentives; Moral Hazard; Multiple Tasks; Fairness; Experiments